Heidegger lettore di Agostino: verso un’ermeneutica della fatticità, attraverso l’esperienza della vita religiosa - Arrien, Sophie-Jan (Bollettino Filosofico, 2020)
The aim of this article is to show how the young Heidegger, in his summer course of 1921, discovers in Augustine, while interpreting Book X of the Confessions, a proto-phenomenologist and hermeneuticist of the factical life (or facticity). We will show that Augustine’s description of Christian religious life offers Heidegger concrete material for the elaboration of his own indicative-formal interpretation of existence, itself subordinated to a strict “methodological atheism”. Keywords: Angst, Augustine, Authenticity, Existentials, Formal Indication